Italy : Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2013)
This Report on Observance of Standards and Codes (ROSC) for Italy summarizes the findings and recommendations of the fiscal assessment of Italy's economic policies. It highlights that while raising the bar for banking supervision, the Core Principles must be capable of application to a wide range of jurisdictions. The new methodology reinforces the concept of proportionality, both in terms of the expectations on supervisors and in terms of the standards that supervisors impose on banks. It recommends that a group-focused supervisory approach for the nationally significant insurers and sophisticated offsite monitoring together with ad hoc inspections for smaller entities is required.